A study of lead content in soils and grass around roadside locations in and around Kuala Lumpur - Low, K. S.; Lee, C. K.; Arshad, M. Yusof (Universiti Pertanian Malaysia, 1979)
Analysis of samples of the grass Axonopus compressus, Beauv. and soil in and around Kuala Lumpur shows the distribution of particulate lead to be strongly influenced by traffic density. In certain areas the lead contamination in grass has reached the toxic level for cattle,. other areas are approaching similar levels. Levels of lead in grass (as high as 200 ppm) at Jalan Tembusu were recorded while soil in the same area gave a value greater than 700 ppm.